Design of tunable surface mode waveguide based on photonic crystal composite structure using organic liquid - 张兰兰 刘伟 李萍 杨曦 曹旭 (Chinese physics B, 2017)
With the method of replacing the surface layer of photonic crystal with tubes, a novel photonic crystal composite structure used as a tunable surface mode waveguide is designed. The tubes support tunable surface states. The tunable propagation capabilities of the structure are investigated by using the finite-difference time-domain. Simulation results show that the beam transmission distributions of the composite structure are sensitive to the frequency range of incident light and the surface morphology which can be modified by filling the tubes with different organic liquids. By adjusting the filler in tubes, the T-shaped, Y-shaped, and L-shaped propagations can be realized. The property can be applied to the tunable surface mode waveguide. Compared with a traditional single function photonic crystal waveguide, our designed structure not only has a small size, but also is a tunable device.